STUDI KELAYAKAN UJI MIKRO KAITANNYA DENGAN CARBON EQIUVALEN PADA LEMBARAN BAJA MAMPU BENTUK ALL KILLED STEEL SHEET SISTEM BATCH ANIL PADA PRODUK LINE BTR, ECL, DAN CRF PT. CRM KRAKATAU STEEL CILEGON - Sukarno, Budi (MAJALAH ILMIAH WIDYA, 2012)
Carbon is a major element in steel. The increment of carbon will be increase the hardness and tensile strength. Composition of 0.85% carbon is easy to be formed and reducing the welding capability. The purpose of this study is to improve the surface properties and raw materials to suit the desired size or according to customer orders. With test method or metallographic micro. The objective of this study is as feasibility of micro testing, related with carbon equivalent in the all killed steel sheet system batch anil in Batch Temperate Roll (BTR), Electro Cleaning Line (ECL) and Cold Roll Finished (CRF) product PT. CRM Krakatau Steel Cilegon. The results shows obtained from the ASTM Standard. Electro Cleaning Line (ECL) on the product line has not occurred grain size. Inclusion on the productÂ Electro Cleaning Line (ECL), Batch Tempered Roll (BTR) and Cold Roll Finished (CRF) dominated by the Stringer Sulfade (SS), Oxide Aluminates (OA), Oxide Silicate (OS), Oxide Glaburator (OG) form. Rating 0 and 1 with the inclusion of 2233, 2333, 2322, and 4322.